Nirmatrelvir/Ritonavir Utilization for the Treatment of Non-hospitalized Adults with COVID-19 in the National Veterans Affairs (VA) Healthcare System - Haley J. Appaneal; Kerry L. LaPlante; Vrishali V. Lopes; Catherine Martin; Laura Puzniak; Timothy L. Wiemken; Evan J. Zasowski; John M. McLaughlin; Aisling R. Caffrey (Infectious Diseases and Therapy, 2024)
Abstract Introduction Limited data exist regarding real-world utilization of nirmatrelvir/ritonavir. We identified predictors of nirmatrelvir/ritonavir use among Veterans Affairs (VA) outpatients nationally. Methods We conducted a retrospective cohort study among outpatients with coronavirus disease 2019 (COVID-19) who were eligible to receive nirmatrelvir/ritonavir between January and December of 2022, to identify factors associated with nirmatrelvir/ritonavir use (i.e., demographics, medical history, prior medication and healthcare exposures, frailty, and other clinical characteristics) using multivariable logistic regression. Results We included 309,755 outpatients with COVID-19 who were eligible for nirmatrelvir/ritonavir, of whom 12.2% received nirmatrelvir/ritonavir. Nirmatrelvir/ritonavir uptake increased from 1.1% to 23.2% over the study period. Factors associated with nirmatrelvir/ritonavir receipt included receiving a COVID-19 booster vs. none (adjusted odds ratio [aOR] 2.19 [95% confidence interval [CI] 2.12–2.26]), age ≥ 50 vs. 18–49 years (aORs > 1.5 for all age groups ≥ 50 years), having HIV (aOR 1.36 [1.22–1.51]), being non-frail vs. severely frail (aOR 1.22 [1.13–1.33]), and having rheumatoid arthritis (aOR 1.12 [1.04–1.21). Those with concomitant use of potentially interacting antiarrhythmics (aOR 0.35 [0.28–0.45]), anticoagulants/antiplatelets (aOR 0.42 [0.40–0.45]), and/or psychiatric/sedatives (aOR 0.84 [0.81–0.87]) were less likely to receive nirmatrelvir/ritonavir. Conclusions Despite increases over time, overall utilization of nirmatrelvir/ritonavir was low. Predictors of nirmatrelvir/ritonavir utilization were consistent with known risk factors for progression to severe COVID-19, including older age and underlying medical conditions. Unvaccinated and undervaccinated patients and those receiving potentially interacting medications for cardiovascular or mental health conditions (antiarrhythmic, alpha-1 antagonist, anticoagulant/antiplatelet, sedative/hypnotic/psychiatric) were less likely to receive nirmatrelvir/ritonavir. Further education of prescribers and patients about nirmatrelvir/ritonavir treatment guidelines is needed to improve overall uptake and utilization in certain high-risk subpopulations.